2007
DOI: 10.1159/000103208
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of New Bone and Fibrous Tissue in the Cochlea following Cochlear Implantation in the Human

Abstract: The formation of new bone and fibrous tissue in the human inner ear following cochlear implantation was evaluated by computer-assisted 3-D reconstruction. Seven temporal bones from patients who in life had undergone cochlear implantation were prepared for histological study with the implant in situ. The specimens were sectioned in the axial plane at a thickness of 20 µm. At least every tenth section was digitally reconstructed in three dimensions and volumes of new bone and fibrous tissue were calculated per m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 38 publications
5
97
1
9
Order By: Relevance
“…Finally, cochlear trauma during surgery and thereby loss of residual hearing leads to reactive fibrosis and ossification inside the cochlea and around the electrode array (5). Such changes could also diminish the ability to stimulate intact neural fibers selectively and thereby be the reason for the plateau in word perception over the long term in the nHP group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, cochlear trauma during surgery and thereby loss of residual hearing leads to reactive fibrosis and ossification inside the cochlea and around the electrode array (5). Such changes could also diminish the ability to stimulate intact neural fibers selectively and thereby be the reason for the plateau in word perception over the long term in the nHP group.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, minimization of cochlear trauma and/or hearing preservation is attempted in all CI surgeries. Although all surgeries should reduce trauma as much as possible, the following are additional reasons for this goal: 1) in patients with considerable residual low-frequency hearing after cochlear implantation, electro-acoustic stimulation, which allows better speech understanding and music perception, is an option (2,3); 2) the benefit from future treatment options such as stem cell therapy may depend on remaining intact cochlear structures (4); 3) less cochlear trauma leads to less intracochlear fibrosis and ossification (5,6), which simplifies revision surgery.…”
mentioning
confidence: 99%
“…Despite the low spiral ganglion cell counts, the patient derived benefit from the implants, with scores of 30% open-set word recognition and 66% on open-set sentences in both ears. Somdas et al [2007] developed a methodology to quantitatively evaluate new bone and fibrous tissue using three-dimensional reconstruction (Amira). They evaluated 7 temporal bones and demonstrated the greatest volume of new bone formation at the cochlear base (consistent with the present results) and at sites of trauma to the lateral cochlear wall in the ascending limb of the basal turn.…”
Section: Discussionmentioning
confidence: 99%
“…One variable might be the distances from the electrodes to the sites of action-potential initiation. These distances depend on a number of conditions that occur in the deafened, implanted cochlea including the position of the electrodes within the scala tympani with respect to the modiolar wall (Saunders et al, 2002); the presence of fibrous tissue and new bone within the scala tympani that obstructs the current path between the electrodes and the neurons (Somdas et al, 2007); and neural pathology that varies along the length of the cochlea, influencing the position of the remaining excitable neurons with respect to each stimulation site (Hinojosa and Lindsay, 1980;Nadol, 1997;Fayad and Linthicum, 2006). Current levels decrease as a function of the distance between the electrodes and the sites of action-potential initiation.…”
Section: Mechanisms Underlying Across-site Patternsmentioning
confidence: 99%
“…Histological studies have revealed several conditions that could lead to variation in the temporal and spatial patterns of responses in neurons stimulated by each of the implanted electrodes. These conditions include various patterns of nerve loss, and the growth of fibrous tissue and new bone in the implanted cochleae (Hinojosa and Lindsay, 1980;Nadol, 1997;Fayad and Linthicum, 2006;Somdas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%